KARAKTERISTIK PETIR DARI AWAN KE BUMI DAN HUBUNGANNYA DENGAN CURAH HUJAN - Deni Septiadi; Safwan Hadi; Bayong Tjasyono (Jurnal Sains Dirgantara, 2011)
This paper describes the relationship between CG (Cloud to Ground) lightning and the rainfall of Bandung and surrounding area. CG lightning data obtained by Lightning Detector that is able to track low frequency of radio signals from electrical processes lightning discharge which installed in Bandung Geophysics Station. For better resolution, data is limited within a radius of 10 km square of study area. Daily analysis during the year 2009 showed a strong relationships between CG and rainfall (r = 0,62 for CG+; r = 0,51 for CG- and r = 0,59 for total of CG). The electrification process dominated by CG- and the peak of CG occurs at MAM with the 43,6% total of CG and occurs at 15.00-17.00 LT. The mature stage occured after 13.00 LT. Keywords:Lightning, CG, Rainfall, Relationship